2010
DOI: 10.1111/j.1540-8191.1998.tb01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Transmyocardial Laser Revascularization in the Treatment of End-stage Coronary Artery Disease

Abstract: Transmyocardial laser revascularization (TMR) has received more acceptance within the last few years. The vast majority of TMR users report impressive clinical benefits. The underlying mechanism for benefit by TMR, however, remains somewhat unclear. Between July 1994 and September 1997, 165 patients underwent TMR at our institution. In three of our TMR patients after an initial angina‐free interval of 1 to 2 years we decided to repeat the laser operation. This article focuses on the three re‐TMR patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Prior to the randomized studies, mortality rates in the 10% to 20% 7‐13 range were reported for TMR patients. In the randomized trials, lower perioperative mortality rates were reported ranging from 1 to 5% 14‐20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the randomized studies, mortality rates in the 10% to 20% 7‐13 range were reported for TMR patients. In the randomized trials, lower perioperative mortality rates were reported ranging from 1 to 5% 14‐20 .…”
Section: Resultsmentioning
confidence: 99%
“…Since the Food and Drug Administration (FDA) approval in 1998, over 20,000 TMR procedures have been performed in the United States and over 50,000 worldwide. Results from individual institutions, multicenter studies, and prospective randomized controlled trials have been reported 7‐20 …”
mentioning
confidence: 99%
“…They reported that although Frazier et al [34] demonstrated a 20% increase in myocardial perfusion, Allen et al [38] showed no significant change when compared to medical management. Furthermore two other papers showed increases in perfusion with thallium scans [40, 41] while three others reported no change [34], [42, 43]. Together, these findings contribute conflicting evidence and inconsistency towards efforts to determine whether or not TMR promotes angiogenesis and/or increased myocardial perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the randomized studies, mortality rates in the 10-20% [7][8][9][10][11][12][13] range were reported for TMR patients. In the randomized trials, lower perioperative mortality rates were reported ranging from 1-5% [14][15][16][17][18][19][20].…”
Section: Results: Sole Therapy Mortalitymentioning
confidence: 99%
“…Additionally, the presence of diseased but non-grafted arteries carries a poor prognosis and poses a significant negative influence leading to an increased incidence of death, recurrent angina, myocardial infarction, and the need for repeat CABG [4][5][6] over 20,000 TMR procedures have been performed in the United States and over 50,000 worldwide. Results from individual institutions, multi-center studies and prospective randomized controlled trials have been reported [7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introduction Historymentioning
confidence: 99%